2006
DOI: 10.1128/cvi.00200-06
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bovine Herpesvirus 4 (BoHV-4) Expressing Glycoprotein D of BoHV-1 Is Immunogenic and Elicits Serum-Neutralizing Antibodies against BoHV-1 in a Rabbit Model

Abstract: Several biological characteristics of bovine herpesvirus 4 (BoHV-4) make it a good candidate as a gene delivery vector for vaccination purposes. These characteristics include little or no pathogenicity, unlikely oncogenicity, the capability to accommodate large amounts of foreign genetic material, the ability to infect several cell types coming from different animal species, and the ability to maintain transgene expression in both undifferentiated and differentiated cells. Bovine herpesvirus 4 (BoHV-4) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…HEK 293T cells were cultured and transfected as previously described (5). Thirty micrograms of pCMV-IgKE2gD-TM was electroporated in HEK 293T cells from a confluent 75-cm 2 flask, and a plasmid expressing green fluorescent protein (GFP) under the control of the cytomegalovirus (CMV) promoter (pEGFP-C1) was identically electroporated (Equibio apparatus; 186 V, 960 F, 4-mm-gap cuvettes) as a negative control and to monitor the efficiency of transfection through the number of green cells.…”
Section: Cellsmentioning
confidence: 99%
“…HEK 293T cells were cultured and transfected as previously described (5). Thirty micrograms of pCMV-IgKE2gD-TM was electroporated in HEK 293T cells from a confluent 75-cm 2 flask, and a plasmid expressing green fluorescent protein (GFP) under the control of the cytomegalovirus (CMV) promoter (pEGFP-C1) was identically electroporated (Equibio apparatus; 186 V, 960 F, 4-mm-gap cuvettes) as a negative control and to monitor the efficiency of transfection through the number of green cells.…”
Section: Cellsmentioning
confidence: 99%
“…Vaccination of cattle with the EHV-1/BVDV recombinant resulted in BVDVspecific, neutralizing antibodies and reduction of viraemia levels and nasal virus shedding after a BVDV challenge infection. This shows that EHV-1 vectors are suitable for vaccination of cattle and may find application in cases where existing antibodies preclude use of live vector vaccines derived from bovine viruses, like the recombinant BHV-4 viruses reported recently which express BVDV glycoprotein E2 or BHV-1 gD [122,123]. Inoculation of the recombinants into rabbits or sheep induced neutralizing antibodies against the respective target pathogens.…”
Section: Herpesvirusmentioning
confidence: 72%
“…A major disadvantage of HSV-1 is its cytotoxicity for many cell types, including neurons, although genetic alterations have been made to reduce its cytotoxicity [ 37 ]. In contrast, we have previously shown that BoHV-4 is able to infect a wide variety of cell types, including neural cells and liver cells, without cytotoxicity [ 46 , 47 ]. These observations suggest that BoHV-4 might have the potential for use as a gene delivery vector for the nervous system and liver.…”
Section: Discussionmentioning
confidence: 99%